wz

Rozklad vύrazω

 

1.      Rozlož na souθin θinitelω:

 

a)      m5 - m2 =            8tu – 10uv =          15a3 +16a4 =             x3y2 + 8x3y3 =            2n3 – 2n =

b)      75c – 45c3 =            18ab2 + 21a2b2 =                      3x2y - 9xy2 =                  p2q4 + q3r2 =

c)      35u3 + 56u =            20ax - 42by =                   105r3 + 63r5 =                          30n2 – 9n =

d)      7ab + 21a2b – 14ab2 =                    5ax + 5bx – 5cx =                       xy3z2 – x2yz3 – x3y2z =

e)      3mn2 – 6mn + 3m =                      20u4 + 32u3 – 4u2 =                     2r5s2 – 14r4s3 + 10r3s4=

f)        a(x + y) + b(x + y) =                 p(r + 2s) – q(r + 2s) =                        x(3y + 7) – (3y + 7) =

g)      x( m – n) + 5(m – n) =              (4 – p) – 2q(4 – p) =                       3d(c + ab) – 8(ab + c) =

h)      x(a – 1) + 2(1 – a) =                  3s(5 – r) + t(r – 5) =                           4(x – y) + 7z(y – x) =

i)        q(p – 4) – r(4 – p) =                   a(c – d) – b(d – c) =                           y(2 – x) – (x – 2) =   

j)        y(3 + z) + 3 + z =                       u( 2 – v) – 2 + v =                              ab(2c + d) + 2c + d =

k)      5x(a – 7) – a + 7 =                     2a2(m  + n2) – m – n2 =                       m2(p – 1) + p – 1 =

l)        3x(4 + y) – 4 – y =                     rs3(t – 12) + t – 12 =                         x(3y + 7) – (3y + 7) =

m)    q( p – 4 ) – r( 4 – p ) =           3a( x2 – 3y ) – 8b( 3y – x2 ) =        2u( v + z ) + 3( v + z ) = 

n)      a2( 2a – 3 ) + ( 3 – 2a ) =   

 

2.      Rozlož na souθin θinitelω:

 

a)      x2 – y2 =         4 – a2 =           b2 – 1 =          25a2 – b2 =            9m2 – 64n2 =            1 – x2 =

b)      z2 – 9 =                  p2 – 49 =               100 – v2 =             c2d2 – 16 =                81p2 – r2q2 = 

c)      –x2 + 16 =                  1 – 36u2 =                    4g2h2 – 100x2y2 =                            -9 + 4c2 = 

d)      x4 – 1 =               p4 – 25q4 =             144m2 – n4 =              a4 – b4 =                x2y4 – a4b2 =

e)      r3 – r =            z3 – z5 =         m5 – m =          4x – x3 =          2a2 – 8 =             5a2 – 20b2 =  

f)        49s2 – 36t2 =         45 – 5m2 =            8x2 – 18y2 =           2ay2 – 2a3 =              7x7 – 28x3 =

g)      10m – 25n =                 15xy – 10xz =               ab + ab2 =                       6a2 – 3a = 

h)      5a2 – 125b2 =           49 – m2n2 =            

           

3.      Rozlož na souθin θinitelω:

 

a)      (a + b)2 – r2 =                    (x – y)2 – 1 =                    25 – (a + 1)2 =               x2 – (u + 3)2 =

b)      (s – 7)2 – p2q2 =                (2x + y)2 – x2 =                                 (m + 2)2 – (2m – 1)2 =

c)      (a – b)2 – (3a + 4b)2 =       (a + 5)2 – (3 + a)2 =                           (3x – y)2 – (x – 5y)2 =

d)      x2 + 2xy + y2 =                16s2 – 8s + 1 =                9 + 6a + a2 =               4+x2 + 4xy + y2 =

e)      p2 – 14p + 49 =                               32 + 16x + 2x2 =                                 4x2 – 48x + 144 =

f)        45x2 + 60xy + 20y2 =                      9a2 – 24ab + 16b2 =                     49a2 + 126ab + 81b2 =

g)      y2 + 1 – 2y =                    -b2 – 2by – y2 =                z2 + 9 + 6z =                     1 + 4t2 – 4t =

h)      –2mn + m2 + n2 =                             -20a – 100 – a2 =                              5a2 + 10ab + 5b2 =

i)        2a2 + 12 + 18 =                                       x2 + 2xy + y2 =                                         4a2 + 4ab + b2 =

j)        27x2 + 90x + 75 =         9p2 + 6pq + q2 =             25 – a2b2 =                 36x2 – 120x + 100 =

 

4.      Rozlož na souθin θinitelω:

 


a)      rs + ry + st + ty =                                                                                            5u + 5 + uv + v =

 

b)      qr + r + q + 1 =                                                                                             ax + bx + cx + dx =

 

c)      3a + 3b + ac + bc =                                                                                       a3 – a2 + a – 1 =